Twenty-one years of hydrological data acquisition in the Mediterranean Sea: quality, availability, and research - A. Ribotti; R. Sorgente; F. Pessini; A. Cucco; G. Quattrocchi; M. Borghini (Earth System Science Data, 2022)
Since 2000, and for the following 20 years, hydrological data of the Mediterranean Sea, with a particular focus on the western and central Mediterranean sub-basins, have been acquired to study the hydrodynamics at both coastal and open sea scales. In total, 1468 hydrological casts were realized in 29 oceanographic cruises planned due to scientific purposes linked with funding research projects but were also sometimes driven by sea conditions and type of vessel. After accurate quality assurance and control, following standard procedures, all hydrological data were included in four online public open-access repositories in SEANOE (SEA scieNtific Open data Edition), available from https://doi.org/10.17882/87567 (Ribotti et al., 2022). Hydrological and dissolved oxygen data are always present in all of the datasets, whereas pH, fluorescence, turbidity, and chromophoric dissolved organic matter (CDOM) are available just for some cruises. Samplings were carried out mainly along transects, with some repetition over the years. The results of two data analyses, i.e., staircase systems in the Tyrrhenian Sea and in the Algero-Provençal sub-basin and spreading of the Western Mediterranean Transient, are mentioned.